Optimisme Dalam Perspektif Hadis - Nur Ah’Syaidah Fitria Ahyati; Mus’idul Millah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
One of the pillars of life is optimism. Human life is greatly influenced by this attitude of optimism. However, many Muslims are beginning to lose hope due to the facts of this contemporary era. When the trials and pressures of life come their way, many people in society become depressed, despairing, or commit suicide or crime. Whereas the Prophet Muhammad favored optimism, because if a person has an optimistic attitude, he will be active, feel happy and will get good. As has been mentioned in many hadith. This study aims to discuss optimism in the perspective of hadith in order to create a good life with Islamic values. The formulation of the problem in this study is how the hadith views related to optimism as an important factor for life and Islamic values. In this research, a qualitative approach is used with the thematic method of hadith. The formal object of this research is the definition, characteristics, and aspects formulated based on the theme of the hadith. Then the results show that the theme of the hadith can be formulated into a terroristic framework about optimism in the perspective of hadith and optimism is very important for human life. The discussion in this study explains that optimism is highly recommended by the Prophet and has a very special place. The conclusion of this study is that optimism is a characteristic that is very important for human life.